Development of problem-solving-oriented mathematics learning tools with TANDUR setting to improve mathematics learning outcomes - Margaretha N. Inna; I Gusti Putu Sudiarta; I Made Ardana (Jurnal Pendidikan dan Pengajaran, 2019)
This study aimed to develop and produce a problem-solving-oriented mathematics learning tool with “tumbuhkan”, “alami”, “namai”, “demonstrasikan”, ulangi”, “rayakan” (grow, experience, name, demonstrate, repeat, and celebrate) (TANDUR) setting to obtain a valid, practical and effective learning tool, and improving mathematics learning outcomes of class X Stone-Concrete Construction at SMK Negeri 1 Denpasar. This research was development research with problem-oriented learning model through TANDUR setting using learning support tools which included student manual, teacher manual and RPP. The development of learning tools followed the development procedure of Plom model which consists of 3 phases, namely: 1) Preliminary Research Phase, 2) Prototyping Phase (iteration process of analysis, design and development, formative evaluation and revision), 3) Assessment Phase (semi summative assessment). The subjects of the study were 28 students of class X KB2 at SMK Negeri 1 Denpasar. The required research data included validity, practicality and effectiveness data of learning tools. The validity of learning devices was tested through expert assessment. While the practicality and effectiveness of learning tools were tested through field trials. The results showed that the developed learning tools were valid with the average score of validation on 1) the student book was 3.7 which categorized very valid, 2) the teacher manual 3.8 which categories as very valid. The practicality of the developed learning tools on 1) implementation of learning devices conducted on field trials I averaging 3.1 which categorized as practical, 2) implementation of learning devices on field II averaging 3.2 which categorized as practical. The developed learning devices were effective with the average of the test score of the learning result on the field trial I was 78.92 with the good category, and the results of field study II was 86.07 with the excellent category which had exceeded the value of the Minimum Completion Criteria.